PENGARUH KOMBINASI MEDIA SAPIH TERHADAP PERTUMBUHAN ANAKAN BALANGERAN (Shorea balangeran Korth. /Burck) - Wahyu Muhammad Akbar; Ahmad Yamani; Sulaiman Bakri (Jurnal Sylva Scienteae, 2020)
Balangeran (Shorea balangeran Korth. /Burck) is one type of wood that has a relatively fast growth compared to other types of peat swamps and this wood has a high quality of robust wood II. Therefore, the researchers conducted a study with a combination of different weaning media to find out the extent of the potential for the life of balangeran saplings with different treatments. The treatment used is treatment K (Top soil100%), A (Top soil 50% + Beach sand 25% + Rice husk 25%) B (Top soil 25% + Beach sand 50% + Rice husk 25%) and C ( Top soil 25% + Beach sand 25% + Rice husk + 50%).This research was conducted at the Shade House of the Faculty of Forestry, Lambung Mangkurat University, Banjarbaru, South Kalimantan. The research experiment a requires complete randomized design with 4 treatments and 15 replications so that there were 60 experimental units. The results of the study showed that the percentage of life of baldons reached 100%. The combination of weaning media did not significantly affect the increase in the height of balangeran puppies while the increase in diameter of balangeran puppies showed a significant effect. The best effect of the combination of weaning media on the growth of baldy tillers was shown by treatment A for (0.11 cm). Baloman seedling biomass was obtained from the calculation of weights from each of the tillers, namely in treatment B (14.23 grams), then treatment K (12.64 grams), treatment A (11.76 grams), while treatment C (9.98 grams).Keyword: Weak Media; Top Soil; Beach Sand; Rice Husk